ChemInform Abstract: Calcium‐Mediated Hydrophosphorylation of Organic Isocyanates with Diphenylphosphane Oxide. Issue 12 (25th March 2014) - Haerling, Stephan; Greiser, Julia; Al‐Shboul, Tareq M. A.; Goerls, Helmar; Krieck, Sven; Westerhausen, Matthias
Abstract The reaction of diphenylphosphane oxide (I) with isocyanates (II) and isothiocyanates (IV) in the presence of a calcium catalyst leads to desired formamides (III) and thioformamides (V), respectively.